PENGEMBANGAN POP UP BOOK BERBASIS LITERASI PADA MATERI KEKAYAAN BUDAYA INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR KELAS IV SD - Lilik Finatul Asyrofiyah; Sri Cacik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop learning media in the form of literacy-based pop-up books on the material of Indonesia's cultural wealth in order to improve the learning outcomes of fourth grade elementary school students. The method used is research and development with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fourth grade students in one of the public elementary schools. The results of validation by material, media, and language experts show that the developed media is very feasible to use in learning with an average validation score of 91. The practicality test showed that the media was very practical, with a teacher response of 98 and an average student response of 92.4. The effectiveness test based on the N-Gain calculation showed that 88% of students experienced an increase in learning outcomes in the moderate to high category, which means that this media is effective in improving students' understanding of the material on Indonesian cultural diversity. The conclusion of this study is that literacy-based pop-up book media is valid, practical, and effective in thematic learning, and is able to foster interest in reading, literacy, and love for the nation's culture from an early age.